Lupus anticoagulant: a clinical and laboratory diagnostic dilemma - Shalini Trivedi; Pooja Jain; Nutan Dixit; Manoj Arun; Udita Singhal (Journal of Pathology of Nepal)
Lupus anticoagulants are a group of diverse autoantibodies that interfere in vitro in phospholipid-dependent clotting tests, and inhibit both the common and intrinsic pathways of coagulation. Paradoxically, they are implicated to cause hypercoagulability, thrombotic events in vivo in varied clinical settings like obstetrics and oncology.